The Beneficial Effects of Trimetazidine on Reperfusion–Induced Arrhythmia in Diabetic Rats - Ramezani-Aliakbari, Fatemeh; Badavi, Mohammad; Dianat, Mahin; Mard, Seyed Ali; Ahangarpour, Akram (Experimental and Clinical Endocrinology & Diabetes, 2019)
Trimetazidine (TMZ), as an anti-ischemic drug, plays a critical role in protecting against cardiovascular complications induced by diabetes. This study was therefore aimed to evaluate the protective effects of TMZ on reperfusion-induced arrhythmias in the diabetic rats. Male Sprague-Dawley rats (250±20 g) were randomly assigned to four (n=8): control rats (C), alloxan induced diabetic rats (D), diabetic rats treated with TMZ (10 mg/kg, D+T10), diabetic rats treated with TMZ (30 mg/kg, D+T30). TMZ was treated orally once daily for 8 weeks. Diabetes was induced by a single intraperitoneal injection of alloxan (120 mg/kg). Ischemia-reperfusion (I/R) was carried out via 30 min of ischemia and following120-min reperfusion. The magnitude and score of arrhythmia, the left ventricular function, infarct size, lactate dehydrogenase (LDH), myocardial creatine kinase (CK-MB) and troponin (cTnI) were measured. The findings were evaluated by two-way repeated measures and one-way ANOVA followed by LSD post hoc test and Fisher's exact test for incidence percentage. The duration, incidence and score of arrhythmia (p<0.001), infarct size (p<0.01) were significantly increased, the cardiac contractility (±dp/dt), LDH, CK-MB (p<0.001) and cTnI (p<0.05) were significantly decreased in the diabetic rats in comparison with the control group. However, treatment with TMZ in the diabetic rats was significantly improved the duration (p<0.001), incidence and score of arrhythmia,±dp/dt LDH, CK-MB, cTnI (p<0.05) and infarct size (p<0.01) in comparison with the untreated diabetic group. The present study indicates anti-arrhythmic effect of TMZ in reducing arrhythmias induced by reperfusion in the diabetic rats.
Keywords: diabetes; trimetazidine; arrhythmia; reperfusion; rats